Faktor Risiko Aspek Lingkungan dan Aspek Perilaku terhadap Kejadian Demam Berdarah Dengue (DBD) di Wilayah Kerja Puskesmas Sukmajaya Kota Depok Tahun 2022: Risk Factors for Environmental Aspects and Behavioral Aspects for the Occurrence of Dengue Hemorrhagic Fever (DBD) in the Working Area of the Sukmajaya Community Health Center, Depok City in 2022 - Rahma, Firda Azkia; Rahayu, Dinda Fenia Sindhi; Prawira, Luqman Yoga; Nandini, Mutiara; Bariyah, Ratu Alfiyatul (Journal of Public Health Education, 2023)
Background: Dengue Hemorrhagic Fever (DHF), commonly known as Dengue Hemorrhagic Fever (DHF), is an acute viral infectious disease caused by the dengue virus belonging to the Arthropod-Borne virus, genus Flavivirus, family Flaviviridae. In 2020, the Sukmajaya sub-district has a high number of dengue cases, there are 153 cases. Objectives: This study aimed to determine the description of risk factors from environmental and behavioral aspects to the incidence of dengue hemorrhagic fever in the working area of Sukmajaya Public Health Center, Depok City. Method: This research method uses a quantitative method with a descriptive approach and in this research, we get 65 respondents by taking data using a checklist. Result: The description of the characteristics of the community shows that women and men have the same opportunity to get DHF, those aged 26-65 years who are vulnerable to being infected, the level of education is still low so they still don't know about prevention of DHF. The description of the behavioral aspect was obtained by respondents whose preventive behavior was good, namely as many as 39 (60%) of respondents and 26 (40%) of respondents whose prevention preventives were not good. An overview of environmental aspects showed that 25 (38.5) respondents found larvae in their homes. And as many as 40 (61.5%) respondents at home did not find any larvae. Conclusion: The results of the health degree study found that the 10 highest diseases in the Sukmajaya Public Health Center, Depok City were against DHF in the first order.